Designing microstructures for sodium reduction - Chiu, N. X. N. (2016)
The aim of this project was to develop the tools and knowledge to reduce dietary sodium by mitigating restrictions to flavour delivery and enhancing saltiness perception through sodium contrast effects in the mouth. This is achieved by restructuring semi-solid and liquid model food systems to achieve maximum flavour delivery for enhanced perception. The project considered two model systems: stable foams and double emulsions. Stable foams were developed to evaluate air inclusions as a potential sodium reduction strategy. Saltiness perception was enhanced as the levels of air inclusion increased and the incorporation of air also increased the delivery of a congruent mushroom aroma, ultimately this resulted in an enhanced overall flavour perception. The release of volatile aroma compounds from the aerated matrix was dependent on the hydrophobicity (Log P) of the volatile. Double water-in-oil-in-water (w1/o/w2) emulsions were evaluated as vehicles to entrap (during storage) and then deliver sodium during oral processing, ultimately to enhance saltiness perception. The emulsions (w1/o/w2) stabilised with a commercially modified octenyl succinic anhydride (OSA) starch (NC46) were able to encapsulate sodium within the inner water phase (w1), retaining 97 % of this sodium for up to 90 d and partially releasing the sodium during oral processing. The release mechanism was the digestion of the stabilising starch by oral α-amylase. When compared to a protein stabilised emulsion, a 23.7 % decrease in overall salt was achieved using NC46 stabilised w1/o/w2 emulsions, without compromising perceived saltiness. To optimise the stability and delivery of sodium from the double emulsion, different levels of OSA modification were evaluated. High levels (3%) of OSA modification increased storage stability and low (0 % OSA) and intermediate levels offered enhanced saltiness. The optimised (1.5% and 2 % OSA) w1/o/w2 emulsion was stable and conferred a 15 % reduction in total sodium without compromising saltiness. These results provide new insights into using colloidal systems to efficiently deliver sodium and aroma volatiles for perception. The sodium redistribution and contrast effects demonstrated in this work may provide new avenues to achieve sodium reduction, particularly in semi-solid and liquid systems.